Impact of COVID-19 Pandemic on Life-Space Mobility of Older Adults Living in Brazil: REMOBILIZE Study - Monica R. Perracini; Monica R. Perracini; Juleimar Soares Coelho de Amorim; Camila Astolphi Lima; Alexandre da Silva; Francis Trombini-Souza; Daniele Sirineu Pereira; Paulo Henrique Silva Pelicioni; Etiene Duim; Patricia Parreira Batista; Renato Barbosa dos Santos; Maria do Carmo Correia de Lima; et al. (Frontiers Media S.A., 2021)
Background: The COVID-19 pandemic hit Brazil in a scenario of substantial socioeconomic and health inequalities. It is unknown the immediate impact of social restriction recommendations (i.e., lockdown, stay-at-home) on the life-space mobility of older people.Objective: To investigate the immediate impact of COVID-19 pandemic on life-space mobility of community-dwelling Brazilian older adults and examine the social determinants of health associated with change in life-space mobility.Design: Baseline data from a prospective cohort study (REMOBILIZE Study).Setting: Community.Subject: A convenience snowball sample of participants aged 60 and older (n = 1,482) living in 22 states in Brazil.Methods: We conducted an online and phone survey using an adapted version of the Life-Space Assessment (LSA). Linear regression models were used to investigate social determinants of health on the change in LSA score.Results: Regardless of their gender and social determinants of health, participants showed a significant reduction in life-space mobility since COVID-19 pandemic outbreak. Life-space mobility reduction was higher among black individuals, those living alone and aged between 70 and 79. Other variables associated with change in life-space mobility, to a lesser extent, were sex, education and income.Conclusion: Social restriction measures due to pandemic caused substantial reduction in older adults' life-space mobility in Brazil. Social inequalities strongly affected vulnerable groups. Concerted actions should be put in place to overcome the deterioration in life-pace mobility amongst these groups. Failure in minimizing health inequalities amplified by the pandemic may jeopardize the desired achievements of the Decade of Healthy Aging.